2018
DOI: 10.1161/jaha.118.008870
|View full text |Cite
|
Sign up to set email alerts
|

Birth Weight and Risk of Type 2 Diabetes Mellitus, Cardiovascular Disease, and Hypertension in Adults: A Meta‐Analysis of 7 646 267 Participants From 135 Studies

Abstract: Background Low birth weight has been associated with increased risk of type 2 diabetes mellitus, cardiovascular disease, and hypertension, but the risk at high birth weight levels remains uncertain. This systematic review and meta‐analysis aimed to clarify the shape of associations between birth weight and aforementioned diseases in adults and assessed sex‐specific risks. Methods and Results We systematically searched PubMed, EMBASE , and Web … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
195
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(227 citation statements)
references
References 100 publications
16
195
1
1
Order By: Relevance
“…In other investigations which tackle the problem of maternal education impact on the offspring BMI the results were similar -the better educated mothers the lower BMI of their offspring [11,17,18]. In the case of birth body parameters we presumed that higher birth body weight is connected with higher BMI values in later stages of life, since 4-56 months of life to adulthood [11,13,14,19].…”
Section: Discussionsupporting
confidence: 58%
“…In other investigations which tackle the problem of maternal education impact on the offspring BMI the results were similar -the better educated mothers the lower BMI of their offspring [11,17,18]. In the case of birth body parameters we presumed that higher birth body weight is connected with higher BMI values in later stages of life, since 4-56 months of life to adulthood [11,13,14,19].…”
Section: Discussionsupporting
confidence: 58%
“…Furthermore, other factors (ie, obesity, ageing, and physical inactivity) are also thought to be important in the timing of the onset and severity of the outcomes . As mentioned, epidemiological evidence suggests that low birth weight, a surrogate marker of prenatal undernutrition, predicts the increased risks of several cardiometabolic conditions later in life; these associations became stronger if low birthweight was combined with a high adult BMI, postnatal compensatory growth, or unhealthy lifestyle factors (ie, smoking, low physical activity, and poor diet), suggesting that the highest risks for cardiometabolic conditions were experienced by those with low metabolic capacity but high metabolic demand . Similarly, the findings of subgroup analyses indicated the potential mediation effects of certain factors in later life, showing that adjustment for age, alcohol, smoking, BMI, or physical activity attenuated or nullified the observed associations in some analyses.…”
Section: Discussionmentioning
confidence: 99%
“…However, if the individuals are subsequently exposed to adequate nutrition or overnutrition in later life, these adaptive responses may increase susceptibility to the development of cardiometabolic conditions in adulthood . Indeed, epidemiological evidence has linked low birth weight, marker indicative of foetal undernutrition, to susceptibility to type 2 diabetes mellitus (T2DM), metabolic syndrome, hypertension, and coronary heart disease later in life. In addition to maternal and foetal nutritional status, low birthweight could also be an indicator of other prenatal factors, such as maternal age, obstetric complications, chronic maternal conditions, maternal body composition, smoking, pollution, and drug use .…”
Section: Introductionmentioning
confidence: 99%
“…[9] Since then, multiple studies have con rmed an established risk of low weight at birth on cardiovascular diseases in adulthood, such as coronary artery disease, myocardial infarction, type 2 diabetes mellitus and hypertension. [9][10][11][12][13] However, only four previous studies have assessed the potential association between BW and the risk of AF, with con icting results. [14][15][16][17] The Women's Health Study of 27,982 women, including 735 AF cases during a median follow-up of 14.5 years, indicated that BW was signi cantly associated with the incident AF among women.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] In addition, numerous studies have suggested that BW is also associated with several cardiovascular risk factors such as type 2 diabetes mellitus and hypertension. [12,13] However, it remains inconclusive whether BW is associated with the risk of AF. To our knowledge, only four previous studies have explored the association between BW and AF, with discordant results.…”
Section: Introductionmentioning
confidence: 99%